Using Fieldworks Language Explorer (FLEx) in the analysis of verbs on educational discourse in online media: A case study in a "full day school" - Isra Mirdayanti (International Journal of Humanities and Innovation (IJHI), 2018)
FieldWorks Language Explorer (FLEx) is an application that provides tools for dictionary development, morphological analysis, decomposition, and so on. Using FLEx application can facilitate researchers in analyzing the discourse quickly and practically. This paper discusses the FLEx application method by giving examples of using the application in analyzing educational discourse on full day school in Indonesia. The discourse is found from several online media, such as: rappler.com, kompas.com, and tempo.co. This analysis is conducted to represent positive and negative verbs in the educational discourse on the topic of full-day school in Indonesia.